2021
DOI: 10.1177/23259671211001773
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Arthroscopic Fixation of Unstable Distal Clavicle Fractures: A Systematic Review

Abstract: Background: Surgical management of unstable distal clavicle fractures (DCFs) remains controversial. Traditional open techniques result in acceptable union rates but are fraught with complications. In response to these limitations, arthroscopic techniques have been developed; however, clinical outcome data are limited. Purpose: The primary purpose was to systematically evaluate the clinical and radiographic outcomes of arthroscopic fixation of unstable DCFs. The secondary purpose was to characterize the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
(82 reference statements)
2
5
0
Order By: Relevance
“…CC rupture is the main factor in fracture displacement in proximal fractures; therefore, CC reconstruction is very important for fracture reduction and maintenance reduction [ 69 71 ]. Yagnik et al [ 22 ] reported that arthroscopy-assisted CC reconstruction of UDCFs reduced implant-related complications and the risk of reoperation, with the same good functional outcomes and union rates as LCP and HP fixation. For UDCFs, especially fractures with a comminuted distal fragments, CC fixation that only fixes the proximal end of the fracture is obviously not enough to achieve the standard of fracture healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CC rupture is the main factor in fracture displacement in proximal fractures; therefore, CC reconstruction is very important for fracture reduction and maintenance reduction [ 69 71 ]. Yagnik et al [ 22 ] reported that arthroscopy-assisted CC reconstruction of UDCFs reduced implant-related complications and the risk of reoperation, with the same good functional outcomes and union rates as LCP and HP fixation. For UDCFs, especially fractures with a comminuted distal fragments, CC fixation that only fixes the proximal end of the fracture is obviously not enough to achieve the standard of fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy regarding the optimal internal fixation method for UDCFs. Several meta-analyses have compared the effectiveness and safety of different internal fixation methods for UDCFs [19,[22][23][24][25][26]. However, published meta-analyses did not include combined fixation methods (i.e., LCP + CC) and had a low level of evidence and high heterogeneity among the outcome parameters due to the small number of papers included.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous surgical techniques used for the fixation of distal clavicle fractures, like using a K-wire or hook plate for direct osteosynthesis and using various suture materials or tendon grafts for indirect stabilization of the coracoclavicular ligament, were without a gold standard procedure [ 7 ]. More evidence suggests that the arthroscopic assisted treatment of displaced distal clavicle fractures is superior to the open surgical techniques because it is relatively durable and minimally invasive procedures with fewer complications [ 8 , 9 ], In addition, the Tight-rope system can self-propelled adjust the reconstructed length, which has been proven to resist higher loads [ 10 ]. In line with previous studies, the present study showed successful clinical and radiological outcomes results for the displaced distal clavicle fractures patients who were treated with arthroscopic assisted fixation using a Tight-rope system, with a statistically significant difference between the preoperative and postoperative constant score, ASES score and VAS score.…”
Section: Discussionmentioning
confidence: 99%
“…Levy et al (15) compared these two techniques (plate and open CC suture stabilization) in the unique type IIC fracture and found better results with the CC stabilization. The superiority of open CC fixation techniques has been recently demonstrated by both Malik et al [ 20 ] and Yagnik et al [ 11 ] who systematically reviewed the arthroscopic-assisted CC stabilization techniques; despite the overall good to excellent shoulder function in both reports, the first one found lower union rates of up to 70% and overall complication rates as high as 28.6%, and the second reported overall complication rates of 27.4%.…”
Section: Discussionmentioning
confidence: 99%